PENYULUHAN DAN PELATIHAN PEMBUATAN PUPUK ORGANIK SERTA PESTISIDA NABATI UNTUK MENUNJANG KEAMANAN PANGAN DI KAMPUNG NASEM - Sembiring, Jefri; Susanti, Diana S.; Prasetia, Andri; Mendes, Johanna (Departemen Budidaya Pertanian Fakultas Pertanian UNHAS, 2020)
The purpose of this service is to build the Nasem village into a safe, friendly and prosperous village of agrotourism by developing organic farming. The current condition of the residents of Nasem village usually still buys the necessities of life from outside the Nasem village, both vegetables and other ingredients. Organic agriculture is a production management system that can improve soil health and the quality of soil ecosystems and crop production. In its implementation, organic agriculture focuses on the use of natural materials that can improve and even improve soil quality. The development and application of the organic farming approach continues to increase along with the increasing clarity of the negative impacts and increasing population awareness about the dangers of using chemicals. Organic farming system that aims to maintain harmony with the natural system, by utilizing and developing as much as possible natural processes in the management of farming. Planting vegetables such as leeks, petsay, cabbage and kale need the right cultivation techniques so that increased production can be in line with the quality of the products produced. The Nasem village farmers do not have the knowledge and skills to grow vegetables after returning from the neighbouring state of Papua New Guinea. For this reason, it is very necessary to conduct training in organic farming skills so that the concept has been applied by the Nasem community from the start. It is expected in the future that Nasem village farmers can produce vegetable products that are free of pesticides and chemical fertilizers. In addition, with the training to plant vegetables organically, it will improve the economy of the community and make people consume healthy vegetables. This service is expected to be carried out continuously.Keywords: Nasem, organic, agrotourism. ABSTRAKPengabdian ini bertujuan untuk membangun kampung Nasem menjadi kampung Agrowisata yang aman, ramah dan makmur dengan mengembangkan pertanian organik. Kondisi pada saat ini warga kampung Nasem biasanya masih membeli kebutuhan hidup dari luar kampung Nasem baik itu sayuran maupun bahan lain. Pertanian organik merupakan sistem manajemen produksi yang dapat meningkatkan kesehatan tanah maupun kualitas ekosistem tanah dan produksi tanaman. Dalam pelaksanaannya pertanian organik menitikberatkan pada peng-gunaan bahan alam yang dapat memperbaiki bahkan meningkatkan kualitas tanah. Perkembangan dan penerapan pendekatan pertanian organik terus meningkat seiring dengan semakin jelasnya dampak negatif dan bertambahnya kesadaran penduduk tentang bahaya penggunaan bahan-bahan kimia. Sistem pertanian organik yang bertujuan untuk tetap menjaga keselarasan dengan sistem alami, dengan memanfaatkan dan mengembangkan semaksimal mungkin proses-proses alami dalam pengelolaan usaha tani. Penanaman sayur-sayuran seperti bawang daun, petsay, kubis dan kangkung perlu adanya teknik budidaya yang tepat sehingga peningkatan produksi dapat selaras dengan kualitas produk yang dihasilkan. Para petani kampung Nasem belum memiliki pengetahuan dan keterampilan untuk bercocok tanam sayur pasca kembali dari negara tetangga Papua New Guinea. Untuk itu sangat perlu dilakukan pelatihan keterampilan bercocok tanam organik sehingga dari awal konsep ini sudah diterapkan oleh masyarakat Nasem. Hal ini diharapkan kedepan bahwa petani kampung Nasem dapat menghasilkan produk sayuran yang bebas pestisida dan pupuk kimia. Selain itu dengan adanya pelatihan bercocok tanam sayur-sayuran secara organik akan meningkatkan perekonomian masyarakat dan membuat masyarakat mengkonsumsi sayuran sehat. Pengabdian ini diharapkan akan dilakukan secara berkesinambungan.Kata kunci: Nasem, organik, agrowisata.